The Theory of Active Intellect in the Thought of Alexander of Aphrodisius - Hasan Abasi Hossain Abadi (آموزه‌‌های فلسفه اسلامي)
Alexander Aphrodisias, a commentator on Aristotle, introduced the theory of intellect and active intellect in his works "On the Intellect of Aristotle")Fi al-'Aql 'ala Aristutalis( and "On the Soul." This theory addresses both the reality and nature of the Active Intellect, as well as its teleological purpose and its relation to human beings. The questions explored in this paper include: What is the nature of the Active Intellect? Is it dependent on human beings or independent? What is its causal role, and what ontological, epistemological, and teleological positions does it hold in Alexander’s theory? Using a descriptive-analytical approach, this paper seeks to clarify these issues. We found that the Active Intellect has both ontological and epistemological functions. It externalizes and has a divine and incorruptible position. Epistemologically, the Active Intellect not only knows itself but also causes the knowledge of intelligibles. From a teleological perspective, the highest goal for human existence is contemplating the highest intelligible. In order to answer these questions, we first briefly introduce Alexander's theory of intellect, and then discuss the theory of active intellect.